2020
DOI: 10.1002/joa3.12427
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation is associated with central sleep apnea in clinic patients undergoing diagnostic polysomnography

Abstract: Introduction Sleep apnea is highly prevalent in patients with atrial fibrillation (AF). Obstructive sleep apnea (OSA) is the most common type, and best studied in the context of AF. However, recent investigations have indicated that central sleep apnea (CSA) may be a risk factor for incident AF. We evaluated the burden of CSA events in patients referred for diagnostic polysomnography (PSG) and whether AF is associated with CSA. Methods We identified patients with and without a history of AF who underwent clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…As AF has also been noted to be associated with CSA, we performed a sensitivity analysis by additionally adjusting for AF to explore this relationship. 16,26,27 In this analysis, which additionally corrected for any AF history, ticagrelor (vs. clopidogrel) became more strongly associated with high CSA burden and became significantly associated with strict CSA (Tables 4 and 5). We did not exclude patients with a history of AF in our primary analysis because the event rate for CSA in our cohort is small, and excluding patients with a history of AF (32.5% of our cohort) would have further lowered the power of our study, as reflected by the large confidence interval.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As AF has also been noted to be associated with CSA, we performed a sensitivity analysis by additionally adjusting for AF to explore this relationship. 16,26,27 In this analysis, which additionally corrected for any AF history, ticagrelor (vs. clopidogrel) became more strongly associated with high CSA burden and became significantly associated with strict CSA (Tables 4 and 5). We did not exclude patients with a history of AF in our primary analysis because the event rate for CSA in our cohort is small, and excluding patients with a history of AF (32.5% of our cohort) would have further lowered the power of our study, as reflected by the large confidence interval.…”
Section: Discussionmentioning
confidence: 94%
“…Because of the reported association of atrial fibrillation (AF) with CSA, we performed analysis additionally adjusting for any history of AF. 16,17 Similarly, an additional subgroup analysis was performed on only patients with ACS due to the high reported prevalence of sleep-disordered breathing in patients with ACS. Statistical analysis was performed through R with gtsummary package.…”
Section: Sleep Studymentioning
confidence: 99%
“…1,2 SA is highly prevalent in AF patients because of the linking mechanisms between SA and AF including activation of the sympathetic nervous system during intermittent hypoxia and structural remodeling of the left atrium through the negative intrathoracic pressure during an obstructive apnea episode. 3,4 Experimental, epidemiological, and clinical studies have consistently shown that SA is a potential risk factor for the incidence and recurrence of AF. 5 A meta-analysis reported that obstructive SA (OSA) is associated with a 31% greater risk of AF recurrence after catheter ablation (CA) of AF.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) and sleep apnea (SA) are common, and both have a risk of cardiovascular morbidity and mortality 1,2 . SA is highly prevalent in AF patients because of the linking mechanisms between SA and AF including activation of the sympathetic nervous system during intermittent hypoxia and structural remodeling of the left atrium through the negative intrathoracic pressure during an obstructive apnea episode 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…The presence of CSA appears to have adverse prognostic implications (21,22). It is important to note that HF results from coexisting OSA and CSA, or complex sleep apnea syndrome (23). However, patients have little understanding of coexistence.…”
Section: Introductionmentioning
confidence: 99%